Identify Barriers that Prevent Adolescents from Accessing Accurate Information about HIV/AIDS - Elok Febrianti; Edi Purwanto (Indonesian Journal of Global Health Research, 2025)
The spread of misinformation about HIV/AIDS can cause misperceptions among the community. The community has a higher tendency to stigmatize people with HIV/AIDS (ODHA). Objective: To analyze the factors that are barriers to accessing accurate information about HIV/AIDS. Method: The research design usescross-sectionalwith data from the 2017 Indonesian Demographic and Health Survey. Bivariate data analysis using chi-squareand multivariate analysis with logistic regression. The sample used for this study was 8,838 respondents. The independent variables in this study were age, gender, education level, employment status, place of residence, wealth index, internet usage, and sources of information from the community. Results: The results of this study indicate that factors that are obstacles in accessing accurate information about HIV include age (OR = 0.948; 95% Cl = 0.909-0.988), education level (OR = 3.986; 95% Cl = 3.557-4.466), place of residence (OR = 0.374; 95% Cl = 0.326-0.429), wealth index (OR = 1.518; 95% Cl = 1.441-1.599) and internet use (OR = 1.419; 95% Cl = 1.229-1.552) are more at risk than others. The conclusion of this study is that the inaccuracy of information received by the community about HIV/AIDS is still high, there are several factors that influence this condition. Conclusions: The most dominant factors related to the spread of inaccurate information are the variables of age, education level, place of residence, wealth index and internet usage. While the variables of gender and employment status do not have a significant relationship.